The Evidence REVEAL Study: Exploring the Use of Real‐World Evidence and Complex Clinical Trial Design by the European Pharmaceutical Industry. Issue 5 (17th December 2020) - Varnai, Peter; Davé, Anoushka; Farla, Kristine; Nooijen, Anke; Petrosova, Liana
Abstract : The rapid evolution of science and technology allows innovative approaches to generate new types of evidence about the effectiveness of medical product development so as to speed up patients' access to better diagnostics and treatment. Our study explored how two emerging approaches, the use of real‐world evidence (RWE) and complex clinical trial (CCT) design, are currently being used by the pharmaceutical industry to support premarketing authorization of medical product development and reviewed the international landscape for regulatory acceptance of such novel approaches. Combining evidence from a literature review, company survey, and interviews with international regulators and experts, we found that 80% of Europe‐based pharmaceutical companies have used RWE and 50% have used CCTs, in some capacity. Further, we present case examples of how companies are using these approaches and how international regulators are preparing for such developments. To conclude, we provide a set of recommendations for European industry and regulators to consider so that these novel approaches achieve their full potential within the EU regulatory system.